Optimización de la extracción de ADN de Passiflora ligularis para el análisis por medio de marcadores moleculares - Gina Solano-Flórez; María del Pilar Márquez-Cardona; Ingrid Schuler (Universitas Scientiarum)
Extraction of high quality DNA of Passiflora ligularis for its analysis with molecular markers. Objective. To standardize a precise andefficient DNA isolation protocol of Passiflora ligularis. Materials and methods. Two methods of DNA extraction and two different tissuesof Passiflora ligularis were evaluated in terms of purity, quality and quantity of DNA yield, as well as DNA’s suitability for moleculartechniques based on PCR such as RAPDs. Quantification of DNA was done using absorbance spectrophotometry at a wavelength of260nm (A260) with a Beckman Du ® 530 spectrophotometer. An estimate of the DNA’s purity was obtained using the absorbance ratio(A260 / A280 nm). The variables analyzed in this study were the extraction method (A) and the tissue type (B), in order to define their influenceon the purity and quantity of the DNA extracted. For the study of these variables a random design with a 2 x 2 factorial arrangement wasused. Results. The average quantities of DNA obtained with the modified method of Mc Couch et al. (1988) and the modified method ofDoyle & Doyle (1991) method were 778.9 μg/ml and 660.1 μg/ml respectively for dry tissue. Averages with fresh tissue were 1543.3 μg/ml and 820.4 μg/ml respectively. Conclusion. Based upon our results we suggest the use of Mc Couch et al. (1988) method with fresh leaftissue to obtain a high quality DNA suitable to be used with RAPDs molecular markers.